Purification and Characterization of a Mitogenic Lectin from Cephalosporium, a Pathogenic Fungus Causing Mycotic Keratitis - Nagaraja N. Nagre; Vishwanath B. Chachadi; Sachin M. Eligar; C. Shubhada; Radha Pujari; Padma Shastry; Bale M. Swamy; Shashikala R. Inamdar (Biochemistry Research International)
Ophthalmic mycoses caused by infectious fungi are being recognized as a serious concern since they lead to total blindness. Cephalosporium is one amongst several opportunistic fungal species implicated in ophthalmic infections leading to mycotic keratitis. A mitogenic lectin has been purified from the mycelia of fungus Cephalosporium, isolated from the corneal smears of a keratitis patient. Cephalosporium lectin (CSL) is a tetramer with subunit mass of 14 kDa, agglutinates human A, B, and O erythrocytes, and exhibits high affinity for mucin compared to fetuin and asialofetuin but does not bind to simple sugars indicating its complex sugar specificity. CSL showed strong binding to normal human peripheral blood mononuclear cells (PBMCs) to elicit mitogenic activity. The sugar specificity of the lectin and its interaction with PBMCs to exhibit mitogenic effect indicate its possible role in adhesion and infection process of Cephalosporium.